1998
DOI: 10.1200/jco.1998.16.11.3563
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery alone or in combination with whole-brain radiotherapy for brain metastases.

Abstract: RS is an effective, noninvasive means of controlling brain metastases when used alone or in combination with WBRT. There is a trend for superior local control and especially in patients without extracranial disease for superior survival when RS is used in conjunction with WBRT. Randomized trials would seem to be warranted, comparing the benefit of RS with or without additional WBRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
142
0
10

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(158 citation statements)
references
References 16 publications
6
142
0
10
Order By: Relevance
“…Long-term toxicity and survival were comparable to SRS results; on the contrary a relatively high incidence of acute/early complications after SRS has been reported in the literature [9][10][11]. The actuarial 1-year local tumor control rate (86.1%) after HSRT was equivalent to that obtained with SRS series (70-90%) in several reports [5][6][7][8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Long-term toxicity and survival were comparable to SRS results; on the contrary a relatively high incidence of acute/early complications after SRS has been reported in the literature [9][10][11]. The actuarial 1-year local tumor control rate (86.1%) after HSRT was equivalent to that obtained with SRS series (70-90%) in several reports [5][6][7][8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 61%
“…They found no significant difference in the median overall survival time (P = 0, 42), while in terms of local and distant intracranial control patients receiving SRS plus WBRT had a better control rate (1-yr actuarial overall control rate 53,2% vs. 23,6; P \ 0,001) [20]. Several retrospective studies, despite the inherent biases, have shown that the omission of WBRT doesn't affect overall survival but has a negative impact on local and intracranial control [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no difference in the clinical outcome whether radiotherapy or neurosurgery is used as an intervention. SRS is mainly advocated in situations with one to three metastases [6,27,38,41], while some studies allow up to five lesions [3,49]. Commonly, a single lesion is treated by a surgical approach.…”
Section: Metastasesmentioning
confidence: 99%
“…SRS offers the ability to tightly conform radiation to the target volume and spare substantial amounts of normal tissue. For properly selected patients, usually those with a limited number of lesions and controlled extracranial disease, many studies show that SRS is as effective as surgical resection for the management of BM, with local control rates as high as 94% [5][6][7].…”
Section: Introductionmentioning
confidence: 99%